2004
DOI: 10.1167/4.3.9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of background color on asymmetries in color search

Abstract: Many previous studies have shown that background color affects the discriminability and appearance of color stimuli. However, research on visual search has not typically considered the role that the background may play. Rosenholtz (2001a) has suggested that color search asymmetries result from the relationship between the stimuli and the background. Here we test the hypothesis that background color should have an effect on asymmetries in visual search based on color, using searches for color stimuli on differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…In humans, it is known that relative contrast between object and background can generate search asymmetries (Nagy and Cone, 1996;Rosenholtz et al, 2004). If search asymmetry in bees is caused by a similar mechanism as in humans, we would predict a lower bee-subjective colour contrast between the blue target and the background and a higher contrast for the yellow target.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In humans, it is known that relative contrast between object and background can generate search asymmetries (Nagy and Cone, 1996;Rosenholtz et al, 2004). If search asymmetry in bees is caused by a similar mechanism as in humans, we would predict a lower bee-subjective colour contrast between the blue target and the background and a higher contrast for the yellow target.…”
Section: Discussionmentioning
confidence: 84%
“…(2) Decision time and error rate are higher when bees search for a blue target within yellow distractors than when they search for a yellow target within blue or mixed-coloured distractors. Bees exhibit a clear search asymmetry in colour search, which is also found in humans when the colours of the target and distractors differ in hue and saturation (Rosenholtz et al, 2004). (3) When target number increases, error rate and decision time decrease.…”
Section: Discussionmentioning
confidence: 97%
“…In a related discussion, Eckstein et al (2000) suggested that the difficulty in searching for conjunctions (Treisman & Gelade, 1980) can be explained by examining the target and the distractors in a high-dimensional visual feature space and by looking into the feature dimensions along which the distractor and the target differ. Similarly, Rosenholtz (1999Rosenholtz ( , 2001 and Rosenholtz et al (2004) suggested that the covariance of the distractors in a higher dimensional feature space may provide an explanation for the difficulty of searching a target in motion or in different color.…”
Section: Introductionmentioning
confidence: 98%
“…However, it is important to note that a limited number of studies have addressed how different feature dimensions contribute to the overall saliency (Callaghan, 1989(Callaghan, , 1990Eckstein, Thomas, Palmer, & Shimozaki, 2000;Rosenholtz, 1999Rosenholtz, , 2001Rosenholtz, Nagy, & Bell, 2004). For instance, it has been argued that for certain tasks some visual features may become visually more salient than others.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, according to [23], [24], and [20], when an object has a certain contrast in relation to the others, it should receive the attention. Then the images 5 and 6, we consider the theories presented in [18] and [25], which is based on the asymmetry credited to the presence or absence of salient features for delivering the attention. In these images, the task of finding the object "+" among "-" is easier than finding the "-" among "+", however the salience should exist in both tasks.…”
Section: B Psychophysic Domainmentioning
confidence: 99%